IMPROVEMENT DAIRY CATTLE BARN MANAGEMENT AFTER FOOT AND MOUTH DISEASE (FMD) OUTBREAK IN MEDOWO, KEDIRI - Permatasari, Dian Ayu; Raharjo, Dadik; Effendi, Mustofa Helmi; Budiarto, Budiarto (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
The Foot and Mouth Disease (FMD) outbreak that began in 2022 caused significant losses for dairy farmers in Medowo Village, Kandangan District, Kediri Regency—impacting both livestock health and farmers' economic stability. To address these impacts, a community service program was carried out to improve farmers' knowledge and skills in dairy cattle housing management and biosecurity implementation. The program included training sessions, educational outreach, and technical assistance for 31 farmers from KUD Kertajaya. Evaluation was conducted through pre-test and post-test instruments to measure the effectiveness of the intervention. Pre-test results showed that only 6.5% of participants were in the "good–very good" category in terms of understanding FMD and livestock management. After the intervention, post-test results showed a significant increase, with 87% of participants reaching the "good–very good" level. Additionally, in terms of practical application of cattle management practices, 100% of participants demonstrated excellent understanding after the program. This intervention proved that an educational approach combining outreach and hands-on practice can significantly enhance farmers' awareness and skills. The improvement is expected to contribute to better livestock productivity and more effective disease control. The activity also involved undergraduate students as part of the Merdeka Belajar Kampus Merdeka (MBKM) program, fostering collaboration between academia and the farming community to strengthen local capacity.